Holy Cross Mission School, lower Yukon River, Alaska, ca. 1914 - Curtis, Asahel, 1874-1941
Large three-story building, with vegetable garden in foreground. Shed and sod hut can be seen in background. On verso of image: Holy Cross Mission, Mission School Notes from unidentified source: For Athabashan and Eskimo children, on lower Yukon River